The Concept of Leader and Leadership in the Qur'an: A Thematic Interpretation Study - Idris Harahap, Mardian; Rusiana, Rusiana; Fizria, Bunga; Mumtaz, Hafiizhah; Nurhalimah, Nurhalimah; Hasibuan, Nur Khomisah (The Future of Education Journal, 2026)
The Qur’an as the primary source of Islamic teachings not only provides guidance on worship and creed but also establishes fundamental principles governing social, political, and governmental life. One of the central themes emphasized in the Qur’an is leadership (imāmah), which is understood not merely as political authority but as a moral and spiritual mandate that entails accountability before both society and Allah. This study aims to analyze the concept of leaders and leadership in the Qur’an through a thematic interpretation approach. Employing qualitative library research, data were collected from classical and contemporary Qur’anic commentaries, scholarly books, and reputable journal articles relevant to Islamic leadership. The study focuses on key Qur’anic leadership terminologies such as khalīfah, imāmah, and ulū al-amr, as well as the ethical principles underlying leadership, including faith, justice, trustworthiness, deliberation (shūrā), and responsibility. The findings reveal that Qur’anic leadership is characterized by moral integrity, justice, and accountability, with obedience to leaders being conditional upon their adherence to divine values. The Qur’an positions leaders as role models tasked with safeguarding public welfare and upholding justice. This study concludes that revitalizing Qur’anic leadership principles is essential for addressing contemporary leadership crises and for building governance systems that are ethical, trustworthy, and oriented toward societal welfare.